PROSESI TRADISI BATAREWAI: DESKRIPSI SINGKAT - Ilham Maulana Priyadi (Universitas Andalas, 2017)
This article describes batarewai procession. Batarewai is a tradition that involves datuak and newly married grooms to parade around the village.Data on this research is obtained through observation, interview, and data testing techniques. Additional data is obtained from books, results of previous studies, and other sources related to this study.There are three stages of the batarewai procession (1) manjapuik datuak (2) kaliliang kampuang (3) naik ka balai adat. The purpose of the batarewai was explained, to introduce the newly married bride and through the nagari discussion.